Estudo de processos redox enzimáticos confinados em eletrodos pelo concomitante monitoramento da variação de massa e da corrente: o caso da penicilinase como modelo - Callera, Welder Franzini Amaral [UNESP] (2013)
The aim of this study was to develop, characterize, and apply the functionalized tranducer imobilized with metalo-β-lactamase (MβL) enzyme using appropriate procedures based on L-cysteine self-assembling monolayer-SAM. The enzymatic activity of MBL under β-lactam antibiotic was measured, on real time, by piezoeletric quartz crystal microbalance (QCM) and eletrochemical techniques. The progress curves were obtained by varying the frequency of quartz crystal. The hyperbolic pattern corresponding to the pattern set on the model of the Michaelis-Menten was not obtained due to low concentration of substrate. On the other side, linear graphic was obtained and the Km was calculated. The Km obtained from electrochemical analyses showed a value similar to manufacturer’s instructions of fabricant, and the Km obtained by QCM showed higher, reflecting the lost of sensibility.